Pengaruh Teknologi Informasi Dan Fitur Layanan Terhadap Keputusan Nasabah Menggunakan Aplikasi BSI Mobile (Studi Kasus Bank Syariah Indonesia KCP Palembang Demang) - Muthiah, Siti Nur; siska , Emi Yulia; ., Lemiyana (CV. ITTC INDONESIA, 2024)
The role of technology in the banking world is absolute, where the progress of the banking system has been supported by advances in information technology. The increasingly developed and complex facilities offered to facilitate service, if the Mobile banking application has complete service features, is easy for customers to use, this is one of the factors that can determine customers' decisions in using the application. This research aims to determine the influence of Information Technology and Service Features on Customer Decisions using the BSI Mobile application (case study of Bank Syariah Indonesia KCP Palembang Demang). The method used in collecting data is through a questionnaire using a Likert scale. The sample used was 100 respondents using purposive sampling. The data analysis technique used for the questionnaire was validity and reliability testing, classical assumption testing, hypothesis testing with data processing using IBM SPSS Statistics version 26. The results of this research show that information technology has no influence on customer decisions, and service features positively and significantly influence customer decisions, besides that information technology and service features simultaneously have a positive effect on customer decisions.